2014
DOI: 10.1007/s10461-014-0759-2
|View full text |Cite
|
Sign up to set email alerts
|

Venues, Patrons, and Alcohol Use Dynamics: The Creation of a High Risk Sexual Environment

Abstract: Venue-based HIV prevention interventions, especially in sex on premise venues, can disrupt high-risk sexual networks. However, prior to intervening, it is essential to understand the person-venue dynamics that contribute to HIV risk. As such, we conducted five ethnographic observations at each of six venues where alcohol is sold and sex occurs onsite (2 each porn theaters, sex clubs, and dance clubs) frequented by gay and other men who have sex with men (G&MSM) in the Buenos Aires metropolitan area. Alcohol us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The results showed a convergence such that venues with the greatest structural risks were most likely to have high population-mixing between locals and tourists, who in turn engaged in the riskiest behaviors. In a different study of six alcohol venues in Buenos Aires, Argentina, researchers conducted five ethnographic observations in each of the venues to richly and comprehensively characterize each place across different dates, patrons, and activities (110). The ethnographers collected information about the area surrounding the venue, characteristics of clientele, personnel and interactions with patrons, areas for alcohol consumption and sexual behavior onsite, condom availability, HIV prevention materials, and other information about events that took place in the venue.…”
Section: How Can We Move Forward With Alcohol Venue Hiv Prevention Rementioning
confidence: 99%
“…The results showed a convergence such that venues with the greatest structural risks were most likely to have high population-mixing between locals and tourists, who in turn engaged in the riskiest behaviors. In a different study of six alcohol venues in Buenos Aires, Argentina, researchers conducted five ethnographic observations in each of the venues to richly and comprehensively characterize each place across different dates, patrons, and activities (110). The ethnographers collected information about the area surrounding the venue, characteristics of clientele, personnel and interactions with patrons, areas for alcohol consumption and sexual behavior onsite, condom availability, HIV prevention materials, and other information about events that took place in the venue.…”
Section: How Can We Move Forward With Alcohol Venue Hiv Prevention Rementioning
confidence: 99%
“…Relatedly, other studies have assessed availability of HIV preventive interventions at venues for social interaction and provided a case for support for venue-based HIV programmes 2 30–32. However, no previous studies identified clusters of high-risk venues despite evidence showing varying prevalence of risky behaviours and availability of HIV prevention programmes in these venues 33. Notably, certain aspects of the physical environment of these venues attract different types of customers and workers.…”
Section: Introductionmentioning
confidence: 99%
“…To construct such programs, ethnographic studies of African bars are critically needed to understand the context, as well as the patterning, of sexual and physical health risks. Examples of such studies from other regions highlight drinking establishment diversity and relate this to intervention/education program feasibility (Balan et al 2014). To accomplish this in sub-Saharan Africa will necessitate additional studies in urban and rural, poor and wealthy, settings.…”
Section: Summary and Discussionmentioning
confidence: 99%